Adductor canal block to manage flexion contracture deformity (FCD) of knee before total knee replacement (TKR) ‐ a case report - Jadon Ashok; Sudarshan Pavan; Sinha Neelam; Chakraborty Swastika (Ain Shams Journal of Anesthesiology, 2020)
Abstract Background The fixed contracture deformity (FCD) which is often present in patients awaiting total knee replacement (TKR) affects the surgical outcome. Therefore, it is necessary to reduce the severity of the FCD before the TKR surgery. Physiotherapy, including active stretching and exercise to increase range of motion are commonly practiced techniques. However, due to the presence of pain, patients are often unable to cooperate and perform exercise up-to the desired levels. We used continuous adductor canal block (CACB) in two patients with severe FCD scheduled for TKR surgery to decrease their pain during physiotherapy and to help them in increasing their range of motion to achieve early fitness for surgery. This approach is not documented and published earlier in the medical literature. Case presentation Two female patients aged 58 and 68 years were scheduled for TKR surgery with severe flexion contracture deformity of both limbs (70°–90°). Due to severe contracture deformity surgeon suggested improvement in ROM before surgery. Ultrasound-guided adductor canal block was given, and catheters were inserted in the adductor canal. Continuous infusion of local anesthetic and bolus injection before active stretching was given. Both patients had good pain relief in existing arthritic pain and pain during active stretching. The flexion deformity was reduced in both the patients up to 30°. The technique of adductor can block with continuous infusion also provided excellent postoperative analgesia and helped in early mobilization without affecting the muscle strength of lower limbs. Conclusion In two patients of severe flexion contracture deformity, the continuous adductor canal block helped to reduce the degree of deformity before the total knee replacement surgery. It also provided excellent pain relief in postoperative pain and helped in early postoperative mobilization without muscle weakness.